Sustainable tourism at Ecuador’s paralelo cero (zero-degree parallel): tourism inventory, markets and local development - Tutillo Vallejo, Adriana (2015)
The Equator Line extends from East to West and passes through the four Ecuadorian regions (The Amazon, Highlands, Coast and Galapagos), thus representing in itself a manifestation of the Ecuadorian natural and cultural diversity. The Ministry of Tourism is seeking to encourage the development of tourist destinations established along and around the Equator Line through the “Ruta Paralelo Cero” initiative. Our objective was to analyze the inventory of tourist destinations, the market and local development, which are of paramount importance for promoting sustainable tourism along the Equator Line. We used methods of geographic and social analysis such as direct observation, interviews with local experts, semistructured surveys, cartographic mapping and geographic information system. We selected three tourist destinations and their surroundings: Highlands, Middle of the World City; Coast, Pedernales; and The Amazon, Cuyabeno Natural Reserve. All these destinations constitute a sample of the Ecuadorian diversity. Our results showed a number of natural and cultural attractions that highlight the potential for tourism at Paralelo Cero. The attractions in the Highlands are among the most visited sites, both by national and international tourists. The tourism demand on the Coast is mainly national, in contrast to that of the Amazon Region, which is mostly international. The greatest challenge for sustainable tourism is to overcome the current inequality in local economic development.